Aqua{N,N-dimethyl-N′-[1-(2-pyridyl)ethylidene]ethane-1,2-diamine-κ3N,N′,N′′}bis(thiocyanato-κN)nickel(II) - Nura Suleiman Gwaram; Siti Munirah Saharin; Hamid Khaledi; Hapipah Mohd Ali (Acta Crystallographica Section E, 2011)
In the title compound, [Ni(NCS)2(C11H17N3)(H2O)], the NiII ion is six-coordinated by the N,N′,N"-tridentate Schiff base N atoms, two cis-positioned N-bound isothiocyanate groups and one water molecule. In the crystal, O—H...S hydrogen bonds link adjacent molecules into infinite layers parallel to the ac plane. The layers are further connected into a three-dimensional network via C—H...π interactions. The –CH2–N(CH3)2 fragment is disordered over two sets of sites in a 0.556 (5):0.444 (5) ratio.